2022
DOI: 10.1155/2022/3143733
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gout with TCM Using Turmeric and Corn Silk: A Concise Review Article and Pharmacology Network Analysis

Abstract: Objective. This work aimed to study the compounds, targets, and pathways of turmeric and corn silk for gout and to explore the mechanism of “the same disease with different treatments” based on network pharmacology and molecular docking. Methods. We used the TCMSP, PubChem, and SEA databases to screen the compounds and targets of turmeric and corn silk, gout-related proteins through TTD, Drugbank, DisGeNET, GeneCards, OMIM, and PharmGkb, and used Cytoscape to construct a “compound-target-disease” network. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The pathogenesis of gout is directly related to increased purine synthesis or high levels of uric acid in the blood. Recently, scholars have conducted a series of studies on the pharmacological effects of corn silk against gout [ 70 ]. Li Ping et al [ 71 ] showed that corn silk flavonoid extract at doses of 0.25 g/100 g, 0.5 g/100 g, and 1.0 g/100 g reduces the serum levels of interleukin-1β and uric acid in rats, indicating that corn silk can treat the joint swelling found in acutely gouty arthritis rats.…”
Section: Pharmacological Actionsmentioning
confidence: 99%
“…The pathogenesis of gout is directly related to increased purine synthesis or high levels of uric acid in the blood. Recently, scholars have conducted a series of studies on the pharmacological effects of corn silk against gout [ 70 ]. Li Ping et al [ 71 ] showed that corn silk flavonoid extract at doses of 0.25 g/100 g, 0.5 g/100 g, and 1.0 g/100 g reduces the serum levels of interleukin-1β and uric acid in rats, indicating that corn silk can treat the joint swelling found in acutely gouty arthritis rats.…”
Section: Pharmacological Actionsmentioning
confidence: 99%
“…According to Comelekoglu et al (2019), exposure to SiO2NPs of 6, 20, and 50 nm diameters may have harmful effects on the hepatic, renal, and brain. Due to oxidative stress, SiO2NPs may cause cytotoxicity and genotoxicity in a range of cell types (Dong et al, 2020;Zhang et al, 2022).…”
Section: Advances Inmentioning
confidence: 99%
“…Traditional Chinese medicine has used turmeric to treat several ailments, including tumors [22]. A common unsaturated phytosterol found in many plants, including turmeric, stigmasterol is a member of the tetracyclic triterpene class [23,24]. Several health advantages and pharmacological properties of stigmasterol, such as anti-in ammatory, antioxidant, and anticancer activities, have been demonstrated [25].…”
Section: Introductionmentioning
confidence: 99%